Building Collaborative Governance in Times of Uncertainty Pracademic Lessons from the Basque Gipuzkoa Province - Barandiaran, Xabier; José Canel, María; Bouckaert, Geert (Leuven University Press, 2023)
Insights and recommendations for collaborative governance. Democratic societies are being challenged to look for new ways of doing politics that involve different stakeholders, particularly citizens. This book looks at public authorities' attempts to put society at the core of public policies in the form of collaborative governance. It provides a full account of a major case from the provincial council of Gipuzkoa (Basque Country, Spain): 150 projects, more than 900 organisations, and 50.000 participants and beneficiaries. 'Pracademic' lessons learned derive from the interaction among 50 practitioners engaged in the day-to-day practice of the case and scholars from different countries. Topics included relate to major challenges that collaborative governance reforms are facing across the world: structures, institutionalisation, relationships, leadership, accountability, innovation, experimentation, communication, intangible resources, trust, and assessment of outcomes (particularly in terms of Sustainable Development Goals or SDGs). Ultimately, issues of democracy arise from a case covering a comprehensive list of policies: health, employment, elderly care, energy, cybersecurity, electromobility, artificial intelligence, immigration, education, social equity, and culture. This book is intended for students, professionals and scholars interested in fostering the study and practice of democracy.